A Newman Error Analysis of Grade 11 Students’ Adaptive Reasoning in Solving Composition-of-Function Problems - Noviana Antaria; Sufyani Prabawanto; Suhendra Suhendra; Ruswan Dallyono (Universitas Pendidikan Mandalika, 2026)
Adaptive reasoning is one of the five strands in mathematical proficiency. It reflects students’ capacity to think logically and justify their reasoning when solving mathematical problems, particularly in the topic of composition of functions. This study aims to analyze students’ errors in solving adaptive reasoning problems on the topic of composition function based on Newman’s Theory. The type of research used is qualitative research using a diagnostic test and interviews as instruments. The subjects of this study were 16 eleventh-grade students at a high school in Berau Regency in Kalimantan Timur Province. The results of this study show that students’ errors occur at the understanding stage, transformation stage, process skills stage, and the solution process stage. In the argumentation indicator, students experienced errors at the comprehension stage by 100%. In the inference indicator, errors occurred at the transformation stage by 43.75% and the process skills stage by 37.5%. Furthermore, on the validation indicator, students’ errors in the process skill stage at 6.25% and the completion process stage at 18.75%. The type of errors that majority of students experienced was the comprehension stage on the argumentation indicator.